A bibliometric study of John Dunning’s contribution to international business research - Ferreira, Manuel Portugal (2021)
This article offers a review of John Dunning’s contribution to international business (IB) research, so as to assess the impact of Dunning and of the Eclectic paradigm on this discipline. The contribution of Dunning and of the Eclectic paradigm – usually referred to as OLI – are a core reference to current international business research, namely for studying location decisions, foreign investment, entry modes and internationalization, and for the multinational enterprise theory. First, we review the conceptual foundations of Dunning’s academic contribution. Second, methodologically, we carry out a bibliometric study of articles published in 14 respected academic business magazines over a period of 31 years, between 1980 and 2010. A sample of 697 published articles that refer to Dunning’s work supports the analysis of citations and co-citations matrixes and of relevant themes, allowing us to verify the influence of Dunning’s work on the international business and Management disciplines. This study allowed us to identify the network of connections between Dunning’s Eclectic paradigm and a variety of international business theories, concepts and authors, as well as with the main subjects studied in the discipline. We observed the connections to the transaction costs theory, resource-based view, industrial organization and evolutionary theory. This study also contributes to scholars’ better understanding of the development of the discipline and of the structure of knowledge within connections between theories and authors. Through their contributions, scholars such as John Dunning leave their imprint on the way in which disciplines and knowledge evolve. Dunning’s work, in the Eclectic paradigm, systematized three conditions that guide the internationalization of companies – and is now a reference for entrepreneurial activities, scholars and research.